A global assessment of Basin Plans: Definitions, lessons, recommendations - Kazbekov, Jusipbek S.; Tagutanazvo, Emelder; Lautze, Jonathan F. (IWA Publishing, 2016)
Basin plans have become a core element of water management in the 21st century. Systematic analytical scrutiny of the contents of basin plans is nonetheless scant. This paper develops a framework for assessing basin plans and systematically applies it to understand how contents of basin plans vary. The paper synthesizes a definition of ‘basin plan’, generates a classification system for basin plans, and proceeds to classify a regionally diverse set of 23 basin plans. Major findings are that basin plans typically contain the components and sub-components suggested in best practice guidelines. Focus on some issues that are presumably central to water management such as water quality and quantity is nonetheless comparatively low. Disaggregating basin plans suggests that developing country transboundary plans are more geared toward hydropower development, navigation and coping with uncertainty, while developed country and national plans appear to focus more on issues such as water quality and fish management. It is hoped that findings contained in this paper support future basin plan development by informing those crafting basin plans of the options available to them.